2018
DOI: 10.15561/20755279.2019.0104
|View full text |Cite
|
Sign up to set email alerts
|

Association between hydration status, hydration knowledge and fluid consumption during training among soccer players

Abstract: Study Aim: The purpose of this study was to determine the correlation between hydration status, knowledge of hydration and the amount of fluid intake consumption during training among the soccer players. Material and Methods: Pre-training hydration status was measured by urine colour chart and Urine Specific Gravity (USG). A questionnaire on hydration knowledge was answered by the participants on the last day of training session. Pearson Correlation test was used to analyse the correlation between hydration st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Eighteen studies recruited participants from one type of sport including swimming ( 9 , 22 , 31 , 49 ) , basketball ( 28 , 30 , 44 ) , soccer ( 41 , 43 ) , gymnastics ( 21 ) , ballet ( 20 ) , rugby ( 57 ) , table tennis ( 23 ) , American football ( 24 ) , cross-country skiing ( 38 ) , handball ( 37 ) , volleyball ( 29 ) and synchronised swimming ( 40 ) . The remaining studies represented various sports, including track and field ( 47 ) , aesthetic sports ( 39 ) , endurance sports ( 34 , 35 ) and various team and individual sports ( 25 27 , 36 , 42 , 45 , 46 ) . Sporting levels included competitive ( 9 , 21 23 , 26 , 30 , 32 , 34 , 35 , 39 , 40 , 42 , 49 ) , regional/state/national competitors ( 27 29 , 36 38 , 43 , 47 ) , high school/college ( 19 , 24 , 27 , 33 , 41 , 45 , 57 ) , elite ( 20 , 44 , …”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies recruited participants from one type of sport including swimming ( 9 , 22 , 31 , 49 ) , basketball ( 28 , 30 , 44 ) , soccer ( 41 , 43 ) , gymnastics ( 21 ) , ballet ( 20 ) , rugby ( 57 ) , table tennis ( 23 ) , American football ( 24 ) , cross-country skiing ( 38 ) , handball ( 37 ) , volleyball ( 29 ) and synchronised swimming ( 40 ) . The remaining studies represented various sports, including track and field ( 47 ) , aesthetic sports ( 39 ) , endurance sports ( 34 , 35 ) and various team and individual sports ( 25 27 , 36 , 42 , 45 , 46 ) . Sporting levels included competitive ( 9 , 21 23 , 26 , 30 , 32 , 34 , 35 , 39 , 40 , 42 , 49 ) , regional/state/national competitors ( 27 29 , 36 38 , 43 , 47 ) , high school/college ( 19 , 24 , 27 , 33 , 41 , 45 , 57 ) , elite ( 20 , 44 , …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it shows good sensitivity, specificity, and precision compared to urine-specific gravity and osmolality measures. A darker urine color (values of 5–8) indicates muscle damage and dehydration, whereas a lighter urine color (values of 1–4) (pale yellow) indicates euhydration [ 35 37 ]. The present study demonstrated that the percentage of change in urine color was positively correlated to the percentage of change in sprinting distance (>25.2 km·h −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study adopted a questionnaire from [7] with good Cronbach alpha value of 0.74. The questionnaire consists of three sections which include: (1) Part A= demographic information, (2) Part B= 10 true or false statements on hydration knowledge (e.g.…”
Section: Questionnaire: Hydration Knowledge and Habitmentioning
confidence: 99%
“…However instead of various guidelines published before, most of athletes did not aware of the sign of dehydration and did not know self-hydration assessment [6][7][8]. According to a study by [9], college athletes generally say that thirst is a clear sign of the beginning of a hydration regimen, but it is already a state where the body is in a dehydration condition.…”
Section: Introductionmentioning
confidence: 99%